Species of Periacma, Irepacma and Epiracma from Taiwan (Lepidoptera: Oecophoridae) - Yin, Aihui; Wang, Shuxia (Zootaxa, 2014)
Six oecophorid species in three genera are recognized in Taiwan, including four new species: Periacma aduncata Wang, sp. nov., Irepacma flagellata Wang, sp. nov., Epiracma longicaudata Wang, sp. nov., and Epiracma annularis Wang, sp. nov. Irepacma conioxantha (Meyrick, 1931) comb. nov. is transferred from Periacma. Images of adults and genitalia are provided.